(untitled) (VERUM: Journal of Scientific Initiation, 2026)
This study aims to analyze the application of involuntary commitment measures for chemical dependents in compliance with constitutional rights. A law sanctioned by President Jair Bolsonaro facilitates the voluntary hospitalization of chemical dependents without judicial authorization and in hospitals and public health units. The hospitalization of a chemical dependent must be considered in accordance with Law No. 10,216, of April 6, 2001, which provides for the protection and rights of people with mental disorders and redirects the care model in mental health. Psychiatric hospitalization shall only be carried out through a detailed medical report that characterizes the reason for hospitalization, and it should only be recommended when outpatient and extra-hospital resources have already proven insufficient for the patient’s case.